Performance of cinnamon and forage grass + legume mixtures under rubber (Hevea) - Pathiratna L S S; Perera M K P (Papers presented at IRRDB seminar 5-8 November 1996 Sri Lanka p26)
Two intercropping systems involving rubber/cinnamon and rubber/forage grasses/tree legumes were investigated. Under immature rubber cinnamon reached harvesting age 2 1/2years after establishment. Cinnamon also performed satisfactorily under mature rubber where light availability for cinnamon was ca. 53;day light. These yields under immature rubber were little low but comparable to that of monocrop Cinnamon. Among the two species of grasses the dry matter (DM) yield of Panicum maximum was almost double of that of Brachiaria brizantha during the first two years but the DM yields of both species declined with the growth of rubber trees. The growth and yield of both species of tree legumes was poor in all treatment combinations. The growth of rubber was not affected adversely by these intercrops during the period of study. i. e. 3 and 5 years with Cinnamon and grass respectively.
Keywords: Cinnamon; Hevea; Intercropping